2011
DOI: 10.1111/j.1747-0803.2011.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Congenital Heart Disease of Mothers: Presentation of a Standardized Questionnaire and First Results

Abstract: The questionnaire covers a range of relevant topics by taking the individual CHD into account. Parents have satisfactory knowledge of CHD in some areas, but knowledge about preventive behaviors turned out as rather poor. This needs to be improved in order to make parents capable to take their share of after-treatment care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Furthermore, prognostic inbetweenness, invisibility, stigma, and drama are wrapped into extreme opposites in the illness trajectory, as seen in the section "Transitions." Finally, as described in this review, the illness trajectory is not equally understood or remembered in the family, and previous research has also found children and youth to lack knowledge and understanding of their CHDs (Janssens et al, 2016;Veldtman et al, 2000), whereas parents overall have a good understanding (Chessa et al, 2005;Löbel, Geyer, Grosser, & Wessel, 2012).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, prognostic inbetweenness, invisibility, stigma, and drama are wrapped into extreme opposites in the illness trajectory, as seen in the section "Transitions." Finally, as described in this review, the illness trajectory is not equally understood or remembered in the family, and previous research has also found children and youth to lack knowledge and understanding of their CHDs (Janssens et al, 2016;Veldtman et al, 2000), whereas parents overall have a good understanding (Chessa et al, 2005;Löbel, Geyer, Grosser, & Wessel, 2012).…”
Section: Discussionmentioning
confidence: 78%
“…Also, the visual subtlety of CHDs, indicated in our review and echoed elsewhere (e.g., Berghammer et al, 2006; Chiang et al, 2015; Messias, Gilliss, Sparacino, Tong, & Foote, 1995), coexists with a stigma and drama around heart conditions found both in the included articles as well as studies on heart conditions in children in general (e.g., Desai, Sutton, Staley, & Hannon, 2014; McMurray et al, 2001), perhaps due to understandings of the heart as a particularly vital organ and its symbolic connection to personhood and life itself (Jensen, 2009, 2011). Furthermore, prognostic in-betweenness, invisibility, stigma, and drama are wrapped into extreme opposites in the illness trajectory, as seen in the section “Transitions.” Finally, as described in this review, the illness trajectory is not equally understood or remembered in the family, and previous research has also found children and youth to lack knowledge and understanding of their CHDs (Janssens et al, 2016; Veldtman et al, 2000), whereas parents overall have a good understanding (Chessa et al, 2005; Löbel, Geyer, Grosser, & Wessel, 2012).…”
Section: Discussionmentioning
confidence: 78%
“…Each decision should be made on a case-specific basis and be thoroughly discussed with the patient to ensure informed consent ( 26 ) especially since a recent clinical study determined the presence of bacteria in the bloodstream following dental care with and without preventive use of antibiotics ( 27 ). The problem of patient’s lack of education, which must be improved in order to help overcome this issue, should also be addressed ( 28 , 29 ). Additionally, communication between physicians that treat the same patient is of great importance since it has been proved that recommendations made by cardiologists had an important influence on both dentists and patients ( 12 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers’ efficient input in terms of their children’s care depends fundamentally on the accuracy of their knowledge about the disease, its symptoms, short- and long-term complications (such as endocarditis), and the preventive rules, besides having good judgmental capacities in critical situations [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…These data emphasize the multifaceted educative role of healthcare professionals in educating caregivers of pediatric CHD patients, which should be much broader than simply providing medical information. Healthcare professionals should regularly ensure that the caregiver’s understanding is appropriate for making timely decisions and compatible with secure long-term patient care [4], [12]. Furthermore, caregivers should be given opportunities to ask questions and provided with sources of additional help and advice [13], as they are often keen to learn more [11].…”
Section: Introductionmentioning
confidence: 99%